The Influence of Zero Waste Packaging Adoption on Café Competitiveness in Medan through Food Delivery Applications - Ginting, Hendro Sutomo; Ravel, Mutiha Aristo; Karo-Karo, Imran (International Journal of Multidisciplinary Sciences and Arts, 2025)
As environmental awareness among consumers continues to rise, the use of eco-friendly packaging has become a potential business strategy to enhance a company’s competitive value. This growing awareness has encouraged culinary businesses to adopt sustainable practices, one of which is the implementation of zero waste packaging. This study aims to analyze the influence of zero waste packaging adoption on the competitive advantage of cafés in Medan City, taking into account the mediating role of customer satisfaction within the context of food delivery service applications. A quantitative approach was employed, using a survey method involving customers who actively use food delivery services from cafés. The theoretical framework is based on the Resource-Based View (RBV) and consumer behavior toward green innovation. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that the adoption of zero waste packaging has a positive and significant effect on café competitiveness, both directly and indirectly through customer satisfaction as a mediating variable. These findings highlight the importance of integrating sustainability values into culinary business strategies to strengthen competitive advantage in an increasingly digital and environmentally conscious era.